Pengembangan Perangkat Pembelajaran IPA Berbasis Inquiry dengan Ajaran Tri N untuk Siswa SMP Kelas VII - Anggraini, Riska Shintya; Wijayanti, Astuti; Sujatmika, Sigit (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2022)
Learning tools are things that must be prepared by educators before carrying out learning activities. Learning tools serve as guidelines and guidelines for teachers in implementing a systematic and integrated learning process. This study aims to find out how to develop and the feasibility of Inquiry-based science learning tools with Tri N teaching for seventh grade junior high school students. This research includes research and development (Research and Development) using the 4D development model consisting of Define, Design, Develop, and Dessiminate. However, the Dessiminate stage was not carried out on this development due to time and cost limitations. The instrument in this study was a questionnaire covering several aspects of the study. The quality of the RPP is assessed by expert lecturers and the quality of the LKPD is assessed by media experts, material experts, student experts, and peer reviewers. Quality value data obtained were analyzed using qualitative and quantitative descriptive analysis based on an ideal assessment. The results showed that Inquiry-based science learning tools with Tri N teaching for seventh grade junior high school students were deemed fit for use in science learning with the assessment of RPP products based on expert lecturers obtaining an idealized percentage of 79.16% and LKPD product assessments based on media experts with a percentage of ideals of 85.23%, material experts 96.42%, student expertise 96.42%, while peer reviewers 85.24%.